Photonic Nanostructures: Photonic Nanostructures Patterned by Thermal Nanoimprint Directly into Organo‐Metal Halide Perovskites (Adv. Mater. 12/2017). Issue 11 (22nd March 2017) - Pourdavoud, Neda; Wang, Si; Mayer, André; Hu, Ting; Chen, Yiwang; Marianovich, André; Kowalsky, Wolfgang; Heiderhoff, Ralf; Scheer, Hella‐Christin; Riedl, Thomas
Abstract : 2D photonic crystals (2D‐PCs) are directly patterned into methylammonium lead iodide perovskite layers by thermal nanoimprint lithography (NIL) at moderate temperatures of only 100 °C, as described in article number 1605003 by Thomas Riedl and co‐workers. The imprinted layers are significantly smoothened and surface defects are eliminated upon thermal imprint. 2D‐PCs afford lasing with ultra‐low lasing thresholds of 3.8 μJ/cm 2 at room temperature, which is indicative of excellent material quality of the perovskite after imprint.